Placental expression of VEGF family mRNA in adverse pregnancy outcomes - Andraweera, P.H.; Dekker, G.A.; Laurence, J.A.; Roberts, C.T. (Placenta (Eastbourne), 2012)
The pregnancy complications preeclampsia, gestational hypertension, small for gestational age infants (SGA) and pre-term birth (PTB) affect approximately 21% of all pregnancies. The Vascular Endothelial Growth Factor family (VEGF) is implicated in the pathogenesis of these complications. We aimed to evaluate the placental mRNA expression of VEGFA, PGF, FLT1 and KDR in pregnancies complicated by preeclampsia, gestational hypertension, SGA infants and pre-term birth. Placentae were collected at delivery from women with pregnancies complicated by preeclampsia (n = 18), gestational hypertension (n = 15), normotensive SGA infants (n = 13), late spontaneous pre-term birth (n = 10) and uncomplicated pregnancy (n = 30). RNA was extracted and VEGFA, PGF, FLT1 and KDR expression were quantified using qRT-PCR. Kruskal Wallis test was used to compare placental mRNA expression in the adverse pregnancy outcome groups compared to uncomplicated term pregnancy. Compared to placental mRNA from uncomplicated pregnancies, VEGFA (p = 0.006), PGF (p < 0.001), KDR (p < 0.001) and FLT1 (p = 0.02) mRNA were reduced in preeclamptic placentae; VEGFA (p < 0.001), PGF (p = 0.01) and KDR (p = 0.008) mRNA were reduced in placentae from pregnancies complicated by gestational hypertension; VEGFA (p = 0.03) mRNA was reduced in normotensive SGA pregnancies; VEGFA (p = 0.008), PGF (p = 0.01), KDR (p = 0.04) and FLT1 (p = 0.02) mRNA were reduced in placentae from late PTB. VEGF family of angiogenic growth factor mRNA expression in the placenta is reduced in gestational hypertensive disorders, SGA and in pre-term birth.